The Economic Recovery Tax Act of 1981 : A Comparative Analysis of Its Impact on Inequality, Poverty, and Real Wages in the United States - Čurilla, Boris (2025)
This thesis examines how the Economic Recovery Tax Act of 1981 (ERTA) affects income distribution, relative poverty, and real median wages in the United States, using Canada as a comparison country over 1975-1988. It deals with the question of whether a major supply-side tax cut brings broad gains in living standards or mainly benefits higher income groups. The analysis uses annual macroeconomic data and a two-country Difference-in Differences model with country and year fixed effects, Driscoll-Kraay standard errors, and controls for GDP per capita, inflation, unemployment, and social spending. The indicators include pre-tax and after-tax Gini coefficients, income shares of the top 1 %, top 10 % and bottom 50 %, a 60% median relative poverty rate, and the real median wage. The results show that ERTA is associated with higher pre-tax inequality and a falling income share of the bottom half of the distribution in the United States relative to Canada. Changes in after-tax inequality, relative poverty, and real median wages remain small and statistically insignificant. The thesis, therefore, nuances the common view of Reaganomics by documenting limited gains for middle and low-income households.